Melanosis as a factor reducing grain quality in proso millet (Panicum miliaceum L.) - Т. V. Kulemina (Труды по прикладной ботанике, генетике и селекции)
Possible causes of melanosis in millet have been studied for a long time, and numerous efforts have been made to breed resistant cultivars, but still there are no sources of high resistance to this disease. The purpose of this article is to provide an overview of the most important results of research into the nature of melanosis in millet, a disease without outward manifestation on plants or seeds, and search for ways to reduce its harmfulness. Although the disease’s infectious nature has been confirmed by all researchers, no one has succeeded in identifying the causative agent of melanosis. It is assumed that melanosis may be provoked by both bacteria and fungi as well as through their complex effect on a plant. Weather conditions conducive to a spread of infection have not been identified either. According to some reports, dry and warm weather increases the risk of infection and spreading of the disease; according to others, more humid and warm conditions are to blame. A possible effect of millet grain shape on the level of disease manifestation has not been clearly explained, but there is evidence that the degree of floral scale closeness and thickness as well as the grain size do enhance mechanical protection of seed from infection. When floral scales are tightly closed, coarsehulled fine grains are as much protected from exposures as possible, which may add to the plant’s defense against the infection. Selecting plants with better developed grain-enclosing scales would help to breed proso millet cultivars resistant to melanosis. The infection can be transmitted by insects, wind or rain from any crop fields infested with the microflora that causes the disease. Its causative agents are specific to a definite area of millet cultivation, which is determined by the temperature regime and indirectly confirmed by conflicting data concerning the effect of air temperature and precipitation on the development of melanosis. The duration of the growing season, in its turn, can also have an impact on the development of damage under the husk of millet grain. Early-ripening millet forms are more resistant to the disease.